Scoateti factor comun pe
(x+√2): a)(x-1)(x+√2)+3(x+√2)
b)2x(x+√2)-5(x+√2)
c)(x+4)(x+√2)-(x-2)(x+√2)
Răspunsuri la întrebare
Răspuns de
44
(x-1)(x+√2)+3(x+√2)=(x+√2)(x-1+3)=(x+√2)(x+2)
2x(x+√2)-5(x+√2)=(x+√2)(2x-5)
(x+4)(x+√2)-(x-2)(x+√2)=(x+√2)(x+4-x+2)=6(x+√2)
2x(x+√2)-5(x+√2)=(x+√2)(2x-5)
(x+4)(x+√2)-(x-2)(x+√2)=(x+√2)(x+4-x+2)=6(x+√2)
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Chimie,
10 ani în urmă